An Analysis of Mimosa pudica Leaves Movement by Using LoggerPro Software. (August 2016) - Sugito; Susilo; Handayani, L; Marwoto, P
Abstract: The unique phenomena of Mimosa pudica are the closing and opening movements of its leaves when they got a stimulus. By using certain software, these movements can be drawn into graphic that can be analysed. The LoggerPro provides facilities needed to analyse recorded videos of the plant's reaction to stimulus. Then, through the resulted graph, analysis of some variables can be carried out. The result showed that the plant's movement fits an equation of y = mx + c.